Evidence for Multiple Phototransduction Pathways in a Reef-Building Coral - Mason, Benjamin; Schmale, Michael; Gibbs, Patrick; Miller, Margaret W.; Wang, Qiang; Levay, Konstantin; Shestopalov, Valery; Slepak, Vladlen Z. (PLOS ONE, 2012)
Photosensitive behaviors and circadian rhythms are well documented in reef-building corals and their larvae, but the mechanisms responsible for photoreception have not been described in these organisms. Here we report the cloning, immunolocalization, and partial biochemical characterization of three opsins and four G proteins expressed in planulae of the Caribbean elkhorn coral, Acropora palmata. All three opsins (acropsins 1–3) possess conserved seven-pass transmembrane structure, and localize to distinct regions of coral planulae. Acropsin 1 was localized in the larval endoderm, while acropsin 2 was localized in solitary cells of the ectoderm. These rod-like cells displayed a remarkably polarized distribution, concentrated in the aboral end. We also cloned four A. palmata G protein alpha subunits. Three were homologs of vertebrate Gi, Go, and Gq. The fourth is presumably a novel G protein, which displays only 40% identity with the nearest known G protein, and we termed it Gc for “cnidarian”. We show that Gc and Gq can be activated by acropsins in a light-dependent manner in vitro. This indicates that at least acropsins 1 and 3 can form functional photoreceptors and potentially may play a role in color preference during settlement, vertical positioning and other light-guided behaviors observed in coral larvae.